Early-Onset Inherited Metabolic Diseases: When Clinical Symptoms Precede Newborn Screening—Insights from Emilia-Romagna (Italy) - Giulia Montanari; Egidio Candela; Federico Baronio; Vittorio Ferrari; Giacomo Biasucci; Marcello Lanari; Rita Ortolano (Children)
Background: Expanded Newborn Screening (ENS) allows the early identification of many inherited metabolic diseases (IMDs) for which timely treatment can modify the natural history. For most IMDs, diagnosis by ENS is pre-clinical. However, clinical symptoms may emerge for certain conditions before screening results become available. Methods: We describe six cases of patients with early-onset IMDs born between 2013 and 2023, who were admitted or transferred to Sant’Orsola University Hospital in Bologna (Italy). Results: Over the study period, 379,013 newborns underwent ENS in the Italian region of Emilia-Romagna. Excluding cases of congenital hypothyroidism, pre-clinical diagnoses from ENS were 410. In addition, six cases of IMD presented with early-onset clinical symptomatology, an antecedent to the outcome of newborn screening (incidence over 11 years of 1.58 cases per 100,000 infants). Among these patients, three were diagnosed with Urea Cycle Disorders (UCDs)—two with Citrullinemia type I (CIT1) and one with Argininosuccinic Acidemia (ASA); two were diagnosed with Methylmalonic Acidemia (MMA); and one was found to have Medium-Chain Acyl-CoA Dehydrogenase Deficiency (MCADD). Conclusions: Our 11-year experience with ENS has shown that clinical onset can occur between the second and fourth day of life, though rare. Even if dried blood spot (DBS) collection was performed 24–48 h after birth, the time required for sample transportation and processing would still delay result availability, making early intervention unlikely. Therefore, our experience supports performing ENS at 48–72 h, as currently implemented in Italy, while also highlighting the advantages and limitations of earlier screening.